The potential of functionalized dressing releasing flavonoids facilitates scar-free healing - Zhang, Mengyuan; Chen, Xiaohang; Zhang, Yuan; Zhao, Xiangyu; Zhao, Jing; Wang, Xing (Frontiers in Medicine, 2022)
Scars are pathological marks left after an injury heals that inflict physical and psychological harm, especially the great threat to development and aesthetics posed by oral and maxillofacial scars. The differential expression of genes such as transforming growth factor-β, local adherent plaque kinase, and yes-related transcriptional regulators at infancy or the oral mucosa is thought to be the reason of scarless regenerative capacity after tissue defects. Currently, tissue engineering products for defect repair frequently overlook the management of postoperative scars, and inhibitors of important genes alone have negative consequences for the organism. Natural flavonoids have hemostatic, anti-inflammatory, antioxidant, and antibacterial properties, which promote wound healing and have anti-scar properties by interfering with the transmission of key signaling pathways involved in scar formation. The combination of flavonoid-rich drug dressings provides a platform for clinical translation of compounds that aid in drug disintegration, prolonged release, and targeted delivery. Therefore, we present a review of the mechanisms and effects of flavonoids in promoting scar-free regeneration and the application of flavonoid-laden dressings.